Relation of Sci-Tech Information to Environmental Studies, 1st edition - Mount, Ellis (Routledge, 2020)
This book, first published in 1990, illustrates the nature and use of sci-tech information in relation to the environment. Sci-tech librarians, government researchers, and compilers and editors of noted indexing/abstracting services describe the efforts of their organizations to compile, maintain, and disseminate the large body of sci-tech information devoted to environmental concerns.